Perbandingan Kejadian Postoperative Nausea Vomiting pada Penggunaan Endotracheal Tube dan Laryngeal Mask Airway pada Pasien Anestesi Umum di RSUD Wates - Wulandari Yulia Anggraeni; Astika Nur Rohmah; Triyas Singgih Pambudi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
General anesthesia is a procedure that eliminates consciousness and pain during surgery. Common devices used to secure the patient’s airway during surgery include the endotracheal tube (ETT) and the laryngeal mask airway (LMA). However, these devices can cause side effects, one of which is postoperative nausea and vomiting (PONV). PONV is a physiological reaction that frequently occurs within the first 24 hours after surgery. This study aims to compare the incidence of postoperative nausea and vomiting in patients undergoing general anesthesia using endotracheal tubes and laryngeal mask airways at RSUD Wates. This study employed quantitative approach with descriptive comparative design. The sample consisted of 40 postoperative patients at RSUD Wates who received either ETT or LMA. The statistical test used was the Mann-Whitney test. The Mann-Whitney test revealed a significant difference in the incidence of PONV between ETT and LMA use, with a p-value of 0.008 (p < 0.05). In the ETT group, 10 respondents (50%) experienced nausea, and 5 respondents (25%) experienced retching or vomiting. In the LMA group, 6 respondents (30%) experienced nausea and 1 respondent (5%) experienced retching or vomiting. There is a significant difference in the incidence of postoperative nausea and vomiting between the use of endotracheal tubes and laryngeal mask airways in patients undergoing general anesthesia.